2022
DOI: 10.3390/rs14143291
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vegetation Greenness and Their Influencing Factors in Southern China

Abstract: Since the 21st century, China has experienced rapid development, and the spatial and temporal changes in vegetation cover have become increasingly significant. Southern China is a representative region for human activities, climate change, and vegetation change, but the current human understanding of the interactions between vegetation and its influencing factors is still very limited. In our study, we use NDVI as the vegetation greenness data, land cover data, temperature, precipitation, downgradient shortwav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 78 publications
4
5
1
Order By: Relevance
“…This study found that vegetation growth in most areas of Guangdong Province displayed an increasing trend during 2001-2020, and the decreasing trend was mainly concentrated in the urban areas and peripheries in the PRD and eastern East MD ecoregions (Figure 3), in agreement with previous studies [9,33]. However, these studies demonstrated a non-significant increasing or even decreasing trend of vegetation greenness in most area of northern Guangdong [9,33], contrasting with our results that vegetation improved significantly in the NG eco-region. This is partially due to the more extended study The contribution type of climate change and human activities to vegetation dynamics was classified under various scenarios (Table 2, Figure 8).…”
Section: Vegetation Trends and Their Climatic Driverssupporting
confidence: 92%
See 4 more Smart Citations
“…This study found that vegetation growth in most areas of Guangdong Province displayed an increasing trend during 2001-2020, and the decreasing trend was mainly concentrated in the urban areas and peripheries in the PRD and eastern East MD ecoregions (Figure 3), in agreement with previous studies [9,33]. However, these studies demonstrated a non-significant increasing or even decreasing trend of vegetation greenness in most area of northern Guangdong [9,33], contrasting with our results that vegetation improved significantly in the NG eco-region. This is partially due to the more extended study The contribution type of climate change and human activities to vegetation dynamics was classified under various scenarios (Table 2, Figure 8).…”
Section: Vegetation Trends and Their Climatic Driverssupporting
confidence: 92%
“…Since both climate variations and human activities have tremendous impacts on vegetation in Guangdong Province [14,33,45], residual trend analysis was used to distinguish the relative impacts of climate change and human activities on vegetation changes [38]. This method assumes that the unexplained variation in the model between vegetation and climatic variables is attributed to anthropogenic activities [60].…”
Section: Residual Trend Analysismentioning
confidence: 99%
See 3 more Smart Citations